Психометричні методи для визначення семантичного ярусу мови - Когут, Лариса Федорівна; Kohut, L. F. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті висвітлено доцільність використання психометричних методів у дослідженнях, які відображають процеси, що відбуваються в дериваційно-епідигматичній ієрархії семантичної структури слова. Методи психолінгвістики, результати яких особливо важливі під час вивчення семантичного ярусу мови, уможливили визначення впливу різних чинників (гендерного, фахового, територіального) на смисловий центр слова, доповнення новими значеннями семантичні ряди ЛСГ, які не зафіксовані в словникових статтях, форму¬вання семантичної системи слова у вигляді словникової статті та розміщення значення відповідно до індексу семантичної ієрархії. Тhе article highlights the expediency of using psychometric methods in researches that reflect the processes occurring in the derivative and epidigmatic hierarchy оf semantic structure of the word. Psycholinguistic methods, the results of which are particularly important in analyzing the semantic layer of the language, made it possible to study the influence on semantic core of speech of various factors (gender, professional or territorial) in the German-speaking environment of Germany and Switzerland. The influence degree of these factors on the semantic structure of the word, in this case, is different: the gender effect was defined to be the strongest, than follows the professional, and the last position is given to the territorial factor. The results of psycholinguistic experiments allowed to define the basic meaning of the word in semantic system, add new meanings into semantic rows of the lexico-semantic group that are not recorded in the dictionary articles, form a semantic system of a word in the form of a dictionary article and place the meaning according to the index of the semantic hierarchy.
Psychometric Methods of the Determantion of the Semantic Layer of a Language
Keywords: епідигматика; epidegmatic; полісемант; polysemant; деривація; derivation